Acessibilidade De Materiais Educativos Para Alunos Com Deficiência: Um Estudo A Partir Da Percepção De Professores Da Educação Básica - Sousa, Raphael Campagnaro Baptista de (2023)
Education is a human right and fundamental. However, this right still remains inaccessible to many students with disabilities. This issue at an educational level is reinforced by a flawed curriculum that does not fairly attend human diversity, as it encourages standardization and, consequently, generates the issue of excluding students with disabilities and other groups in teaching materials and methods. Within this research problem, we propose to carry out an analysis, focused on the adaptation of educational materials of regular High School from the perception of their teachers, at the same time that we provide moments of teaching reflection for the assistance of students with disabilities. In order to achieve our main goal, we set out as specific objectives: (i) verify the position of a group of High School teachers, regarding the use of standardized didactic material from a large teaching network to assist students with disabilities; (ii) propose to a group of private High School teachers, moments of reflection and awareness about their inclusive teaching practices and (iii) discuss the accessibility of High School biology educational materials in handouts, proposed by a private school associated with a large national education network. The theoretical framework that supports the present study draws on the contributions of Arroyo (2006, 2010, 2011, 2012, 2013, 2016) added by Pimenta (1996), Libâneo e Pimenta (1999) and others. From a methodological point of view, this is a qualitative study with an exploratory nature that involves the application of a virtual questionnaire, two conversation circles, the holding of a workshop and a documental analysis of the biology educational material in handout from a large private network of national education, to which the school in question is associated. Regarding the results obtained, we found that the objectives and hypotheses of the research were in line with the proposition that the conversation circles and the workshop about inclusion proposed to High School teachers can favor moments of reflection on their teaching practices and that the positioning of the participating teachers contributed to reinforce that the analyzed educational material in handout needed adjustments, in order to attend the proposal of a more accessible teaching to a naturally heterogeneous classroom. We also concluded that possible adjustments to be made in the didactic material analyzed suggest the use of Assistive Technology (AT), aligned with the use of Universal Design for Learning (UDL). However, even with such adjustments, this material still has gaps in its accessibility. These adjustments were also the responsibility of the multidisciplinary team involved in the educational process, since apparently, the educational system that produced the analyzed educational material in handout is not concerned with providing its users with better accessibility conditions, which favors the construction of a competitive and excluding education.(AU)